A preliminary evaluation model for reservoir hydrocarbon generating potential established based on dissolved hydrocarbons in oilfield water - 赵红静 孙玮琳 何保田 梅博文 张敏 (Acta geochimica, 2006)
A large number of oilfield water samples were analyzed in this work. Research on the relationship between the concentrations and distribution of dissolved hydrocarbons suggested that the contents and composition of dissolved hydrocarbons varied with the hydrocarbon-generating potential of reservoirs. The concentrations of dissolved hydrocarbons were low in dry layers, water layers and gas-water layers, but high in gas reservoirs and oil reservoirs, especially in gas reservoirs with condensed oil. Series of carbon-number alkanes were usually absent in oilfield water from dry layers, water layers and gas-water layers but abundant in oilfield water from oil-water reservoirs, gas reservoirs and oil reservoirs, whose carbon numbers varied most widely in oil reservoirs and least in gas reservoirs. A preliminary evaluation model for reservoir hydrocarbon-generating potential was established based on the characteristics of dissolved hydrocarbons in oilfield water to assist hydrocarbon exploration.